Quality of life and scar evolution after negative pressure or conventional therapy for wound dehiscence following post‐bariatric abdominoplasty. Issue 6 (1st March 2017) - Limongelli, Paolo; Casalino, Giuseppina; Tolone, Salvatore; Brusciano, Luigi; Docimo, Giovanni; del Genio, Gianmattia; Docimo, Ludovico
Abstract : No studies have examined scars and quality of life after different treatments of wound dehiscence in patients undergoing post‐bariatric abdominoplasty. Scars and quality of life of patients with postoperative wound dehiscence managed with negative pressure wound therapy (group A) and conventional wound therapy (group B) were reviewed 6 months after wound healing. Of 38 patients undergoing treatment for wound dehiscence after 203 abdominoplasty, 35 (group A = 14 versus group B = 21) entered the study. Wound healing in group A was significantly faster than group B ( P = 0·001). Patients ( P = 0·0001) and observers ( P = 0·0001) reported better overall opinions on a scar assessment scale for group A. Better overall quality of life and general health satisfaction were observed in group A ( P < 0·05). A significant correlation was observed between the World Health Organization Quality of Life scores and Patient and Observer Scar Assessment Scale scores ( r =−0·68, P < 0·0001) in all 35 patients. Negative pressure wound therapy is feasible and effective in patients with wound dehiscence following post‐bariatric abdominoplasty. An adequate post‐treatment outcome is achieved compared with conventional wound therapy in light of a strong association found between worse patient scar self‐assessment and poor overall quality of life, regardless of the received treatment.